A study of the changes in pelvic floor biometry in pregnancy by trans labial ultrasonography: cross sectional observational analytical study - Singh, Mamta; Bharti, Shikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The pelvic floor, a crucial structure for urinary and anal continence, sexual function, and pelvic organ support, undergoes significant changes during pregnancy and childbirth. Damage to this area can lead to female pelvic floor disorders (FPFDs) such as urinary incontinence, fecal incontinence, and pelvic organ prolapse. This study aimed to evaluate the changes in pelvic floor biometry during pregnancy using translabial ultrasonography (USG) in Indian women. Methods: This cross-sectional observational analytical study recruited 112 women from December 2022 to July 2023 at Sparsh Hospital. The participants included nulliparous women (n=12) and pregnant women in their second and third trimesters, divided into primigravida (n=50) and second gravida (n=50) groups. Translabial 2D and 4D USG was performed in the study. Results: The study found statistically significant changes in bladder neck mobility and hiatal area in primigravida patients compared to nulliparous women. Bladder neck mobility increased with parity, especially during the Valsalva maneuver, suggesting a greater descent in multiparous women. The thickness of the levator ani muscle also increased during pregnancy, showing a significant change during contraction in primigravida patients. While hiatal area did not significantly change with increasing parity, bladder neck mobility was notably higher in second gravida patients compared to primigravida patients, particularly during contraction. Conclusions: Translabial USG is a valuable, non-invasive tool for assessing these changes, which can help clinicians and patients anticipate potential PFDs and implement preventative post-delivery care.